Analisis Kekuatan Tarik dan Metalografi Sambungan Spot Welding pada Material AISI 321 - Handi Handi; Permana Andi Paristiawan; Necko Junia (JURNAL TEKNOLOGI INDUSTRI, 2026)
This study aims to analyze the tensile strength and metallographic characteristics of spot welded joints using AISI 321 material. The joining process was carried out using the resistance spot welding (RSW) method with a lap joint configuration under constant welding parameters. The welded specimens were subjected to tensile testing to determine the maximum load and the type of failure. In addition, metallographic examination was conducted to observe the microstructural changes in the welded region. The results show that the maximum tensile strength obtained is 1.483 N/mm2, with the failure mode identified as interfacial failure. Metallographic analysis reveals three main zones: base metal, heat affected zone (HAZ), and fusion zone. The microstructure in the nugget area tends to be finer due to rapid cooling, while grain growth is observed in the HAZ as a result of the thermal cycle during welding. The correlation between tensile test results and metallographic observations indicates that the joint quality is strongly influenced by the nugget size and microstructural characteristics, particularly in the HAZ region. Therefore, welding parameters play a crucial role in determining the mechanical performance of spot welded joints.